Persepsi dan Penilaian Konsumen terhadap Risiko Halal Rantai Pasok Bakeri - Ash-Shidiqie, Azkia Yasna Nadhratuzzaman; Cahyadi, Eko Ruddy; Hidayatulloh, Furqon Syarief (JURNAL AGROINDUSTRI HALAL, 2025)
Halal is an important aspect for Muslim consumption. Innovation in food industry encourages business actors to maintain quality and halal assurance. The business process of bakery has contamination risks at every stage. Therefore, consumer awareness and thoroughness are crucial in choosing halal and thoyyib food. However, consumers often ignore the halal risk. Therefore, this study aims to determine the consumer perception of the halal risk of bakery. This research used a quantitative descriptive approach by distributing questionnaires. Halal supply chain risk assessment was conducted using FMEA method based on the plan, source, make, deliver, and return subprocesses. The results showed that the halal aspects, raw materials, production processes, and packaging according to halal standards were the most considered aspects by bakery consumers. The results of the halal risk assessment obtained 11 risk priorities based on the RPN value. The results showed that the highest risks from retail were the packaging damage, contamination from employees and product displays, and the difficulty of product returns by consumers. Potential risks at the producer are products do not have halal certificate and contamination from shipping transportation. Potential risks at the supplier were the packaging and meat ingredients that do not have halal supporting documents.